2019
DOI: 10.5606/archrheumatol.2019.7120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Real-Time Tissue Elastography and Gray-Scale Ultrasound Histogram Analysis in the Diagnosis of Patients With Sjögren’s Syndrome

Abstract: Objectives: This study aims to evaluate gray-scale histogram analysis of B-mode ultrasound (US) images and US elastographic features of the parotid glands in patients with Sjögren's syndrome (SS) and to explore relationships with the ultrasonographic and disease activity scores in the light of histopathological findings. Patients and methods: A total of 57 consecutive female patients (mean age 47.9±10.4 years; range 25 to 76 years) with a diagnosis of SS and 48 healthy female individuals (mean age 51.1±10.8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Gray-scale histogram analysis of US images is a more objective method, 39 which can quantitatively provide echogenicity information of lesions according to the echo intensity level in the gray range of 0 to 255. 16 , 39 , 40 Thus, some subjective or operator-dependent features in conventional US evaluation can be effectively eliminated. 39 , 40 To date, many literatures have reported that gray-scale ultrasound histogram is helpful to evaluate different lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray-scale histogram analysis of US images is a more objective method, 39 which can quantitatively provide echogenicity information of lesions according to the echo intensity level in the gray range of 0 to 255. 16 , 39 , 40 Thus, some subjective or operator-dependent features in conventional US evaluation can be effectively eliminated. 39 , 40 To date, many literatures have reported that gray-scale ultrasound histogram is helpful to evaluate different lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 39 , 40 Thus, some subjective or operator-dependent features in conventional US evaluation can be effectively eliminated. 39 , 40 To date, many literatures have reported that gray-scale ultrasound histogram is helpful to evaluate different lesions. 11 , 15 , 16 , 39–41 For example, Kwon et al 16 proposed that grey-scale US was an easily applicable and standard imaging modality used to evaluate thyroid nodules, and some grey-scale histogram parameters could be helpful for the discrimination between the subtypes of follicular variant of papillary thyroid carcinoma (FVPTC).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study was that although we used the Kager fat pad as a reference tissue, we do not have clear information about the effects of CKD on the Kager fat pad. Nevertheless, we picked fat tissue as a reference because it was considered relatively constant, similar to several past studies using fat tissue as a reference, including those with Achilles tendons as well as other subjects, including breast and parotid studies 6,21 . The use of external reference material could have excluded this limitation, as used by some investigators in their past studies 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the traditional and high-resolution US evaluation (36)(37)(38), recently quantitative evaluation of parotid gland echogenicity by means of grey-scale histogram measurements (ROI) was also reported. The gland histogram ratio (mean grey-scale histogram parotid/ mean grey-scale histogram subcutaneous fat) on healthy subjects and patients with parotid abnormalities can be also determined (39)(40)(41).…”
Section: Gsusmentioning
confidence: 99%